Мотиви дороги у книзі поезії «гніздо висоти» Михайла Жайворона - Крупка, Віктор (Українська література: історичний досвід і перспективи, 2023)
The article outlines the motives of the road in the book of poetry «Gnizdo Vysoty (The Nest of Height)» by Mykhailo Zhaivoron. The main attention is paid to the road as a symbol of the life cycle, the path of life, when the designated motif becomes an artistic expression of the process of existential-creative and social identification, existential choice. An important factor in the formation of this content aspect in the poetic work of the writer is its inclusion in the Cosmo-Psycho-Logos as an informational and value code of Ukrainianness, when the trinity of man (body, spirit, soul) is realized in the unity of Ukrainian nature (Cosmo), the character of the people (Psyche), manifested in its mentality/mind/experience (Logos). Undoubtedly, the national images of the world acquire a unique expression in Mykhailo Zhaivoron’s lyrical works, which gives grounds for inscribing motif-figurative parameters into their structure. Motives of the road are also manifested at the level of the own / other category. The specified interpretive model is defined by three perspectives: national, foreign cultural and ethical, in each of which the Ukrainian appears as the image of a prodigal son. Returning (the way home) gives a chance for happiness, non-returning — dooms one to spiritual wasteland, constant wandering, misunderstanding of one’s place in life. In the manifestation of the rites of the seasons, this meaningful aspect acquires a secondary sound, becomes a chronotopic interval, a detail, an insignificant stroke that connects autumn with winter, winter with spring, spring with summer, summer with autumn, and creates a kind of cycle, saturated with vivid moments of the connection between human and nature. After all, roads in a person’s life and roads in the interweaving of seasons are different in their ultimate goal, but they are united by their original essence and procedural reality.